Proposed Marketing Strategy to Increase Foreign Surfers Intention to Visit Ciletuh-Palabuhanratu Unesco Global Geopark (The Indonesian Journal of Business Administration, 2021)
Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGGp) is the first West Java Geopark located in Sukabumi Regency, and received UNESCO Global Geopark status in 2018. As a tourist spot, CPUGGp provides three geoparks that attract tourists, such as: earth diversity, biodiversity, and cultural diversity. Although CPUGGp had the highest number of visitors in 2018 with 1,175,258 visitors, compared to foreign visitors who came to Indonesia in 2019, GGPG in 2019 fell by 26% to 873,894 visitors, and CPUGGp still 1% of them. The theoretical method of this research is to use customer analysis, perform external analysis of the general environment (PESTEL) and industrial environment (Porter 5 Forces), and perform an internal analysis of a resource-based model. The methodology used for customer analysis uses multiple regression analysis. Education, relaxation, joy, comfort, attraction, intimacy with locals and a variety of destination activities. At the same time, the visit intention is the dependent variable. It turns out that the results that affect the intention of the visit are interest, intimacy with the surrounding community and various destination activities. The results of this analysis will be developed as a comprehensive marketing communication strategy to achieve surfers’ motivation, which is expected to increase their willingness to visit CPUGGp. Keywords: Motivation; Geopark; Ciletuh UNESCO global Geopark; Internal Analysis: External Analysis; Customer Analysis; Surfer